An experimental analysis on tar cracking using nano structured Ni-Co/Si-P catalyst in a biomass gasifier-based power generating system. (25th March 2016) - Kannaiyan, Shanmuganandam; Madhavan, Venkata Ramanan; Rajagopal, Saravanan; Jayabalan, Anichai
Highlights: Nano structured Ni-Co/Si-P catalyst was synthesised by DPM. Baseline tar value of 1.8 g/Nm 3 was observed at optimum ER of 0.3. Tar mitigation efficiency of 99% was achieved using nano Ni-Co/Si-P catalyst at catalytic bed temperature of 800 °C. Abstract: Adoption of biomass gasification-based power generating systems for meeting the power requirements of decentralised habitations on kW scale is not only a proven option but is also regarded as an environmentally benign approach. One of the persisting issue still to be resolved in biomass gasifiers is the formation of tar along with the producer gas. Tar is regarded as highly carcinogenic and is observed to condense at room temperature, thereby blocking and fouling the downstream equipment's. Among the tar mitigation methods, catalytic tar mitigation method is highly effective, and majority of the studies have been conducted with bulk catalysts, which suffer due to inherent disadvantages. Hence it has been proposed to experimentally analyse the impact of nano catalytic-based tar reduction to overcome the said drawbacks. The objective of this study is to evaluate the effectiveness of a novel low-cost, eco-friendly bimetallic nano structured Ni-Co/Si-P catalyst for tar removal in a downdraft 15 kWth biomass gasifier. The nano catalyst was synthesised by deposition–precipitation method. Characterisation of the catalyst has been accomplished using XRD, HR-SEM, HR-TEM, BET and TGA analysis. Using XRD pattern the mean size of nano crystallite particles has been observed in the range of 10 nm. HR-SEM and HR-TEM measurements concur with this value. BET analysis using N2 sorption studies revealed the surface area as128 m 2 g −1 . TGA studies confirmed that the catalyst was thermally stable up to 900 °C. The gas generated from the gasifier was made to pass through a catalytic tar cracking unit comprising Ni-Co/Si-P nano catalyst. Experimentation with the nano catalyst resulted in a tar cracking of 99% as compared to 91.5% from bulk mode. Hence it has been conjectured that nano Ni-Co/Si-P catalyst is capable of mitigating the tar generated in biomass gasification systems substantially.